Long‐term survival of a dog diagnosed with a primary multicentric hepatic plasma cell tumour treated with surgery and chemotherapy. Issue 3 (29th June 2021) - Pierini, Alessio; Binanti, Diana; Marchetti, Veronica; Speca, Matteo; Pisani, Guido
Abstract: A 7‐year‐old, intact, female Jack Russell terrier was presented for evaluation of a mammary nodule. Abdominal ultrasonography for initial staging revealed a 1 cm hypoechoic nodule within the left lateral hepatic lobe (LLHL), which was histologically determined to be a plasma cell tumour (PCT). Computed tomography revealed an additional 5 mm nodule in the right medial hepatic lobe (RMHL). Exploratory celiotomy showed that the PCT in the LLHL adhered to the gastric wall. Partial liver lobectomy and partial gastrectomy were carried out to remove the PCT in the LLHL. Marginal excision was done to remove the RMHL nodule, which was determined to be a PCT. The dog was treated with prednisone and melphalan for 6 months and remained in complete clinical remission for 37 months. Surgery and adjuvant chemotherapy were successful in maintaining long‐term remission in this patient. This is the first report of primary multicentric hepatic PCT in a dog.